Manufacturing method of electrolytic capacitor

The proposed method for manufacturing electrolytic capacitors addresses the issue of terminal thickness defects by incorporating step portions on the lead frames and controlling the heat treatment temperature, resulting in improved product quality and reduced defects.

JP7647722B2Active Publication Date: 2025-03-18MURATA MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022172473
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2025-03-18
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

The existing manufacturing method for solid electrolytic capacitors results in thickness defects of the terminal portion due to the melting and flow of Sn during heat treatment, leading to potentially defective products.

Method used

The method involves preparing a workpiece with a sealed body containing electrolytic capacitor elements and lead frames, forming step portions on the lead frames, and performing heat treatment at a temperature higher than the melting point of Sn but lower than that of Cu, with the lead frame having the step portion positioned upward. This prevents excessive Sn accumulation and reduces terminal thickness.

Benefits of technology

This approach effectively suppresses the thickness defect of the terminal portion, reducing the risk of defective products and ensuring the manufacturing process achieves the desired terminal thickness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647722000002
    Figure 0007647722000002
  • Figure 0007647722000003
    Figure 0007647722000003
  • Figure 0007647722000004
    Figure 0007647722000004
Patent Text Reader

Abstract

To provide a manufacturing method of an electrolytic capacitor, enabling suppression of thickness defect of a terminal portion.SOLUTION: A manufacturing method of an electrolytic capacitor includes: a step of preparing a workpiece 100 comprising a sealing body 110 and a first lead frame 120 and a second lead frame 130 that are connected to one of a positive electrode and a negative electrode of an electrolytic capacitor element; a step of providing a level difference portion 150 in at least one of a first main surface 120a and a second main surface 120b of the first lead frame; a step of performing a heat treatment on the workpiece in a temperature higher than a fusion point of a low fusion metal and lower than a fusion point of Cu while the first lead frame comprising the level difference portion is provided in an upper direction and the second lead frame is provided in a lower direction; and a step of cutting the first lead frame between the sealing body and the level difference portion after the heat treatment. The first lead frame includes base material comprised of Cu, and includes in the surface thereof, a low fusion point metal layer comprised of the low fusion metal having the fusion point lower than that of Cu.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing an electrolytic capacitor. [Background technology]

[0002] Patent Document 1 describes a solid electrolytic capacitor that includes an insulating resin body having multiple capacitor elements disposed therein, and a pair of terminals (lead frames) that are electrically connected to the anode and cathode portions of each capacitor element, respectively. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2020 / 179170 Summary of the Invention [Problem to be solved by the invention]

[0004] The solid electrolytic capacitor described in Patent Document 1 is usually manufactured through the following steps. First, a plurality of capacitor elements are manufactured. Next, a plurality of capacitor elements are stacked, and a lead frame is electrically connected to the cathode and anode of each capacitor element. Each lead frame has, for example, a base material made of Cu, a Ni layer formed on the surface of the base material, and a Sn layer formed on the surface of the Ni layer. Next, the plurality of capacitor elements are sealed with an insulating resin. At this stage, the lead frame is not yet bent, and extends straight from the insulating resin body to one side and the other side. Then, with one lead frame facing upward and the other lead frame facing downward, a heat treatment (aging treatment) is performed at a temperature higher than the melting point of Sn and lower than the melting point of Cu. This allows screening of individuals with poor quality. Then, each lead frame is cut to remove unnecessary parts. Then, each cut lead frame is bent to form a pair of terminals.

[0005] In this manufacturing method, the temperature of the heat treatment is higher than the melting point of Sn, so Sn melts during the heat treatment and flows downward due to gravity. Therefore, after the heat treatment, in the lead frame located at the top, Sn gathers near the insulating resin body, so the terminal formed from the lead frame becomes thick. In particular, it is the worst if Sn solidifies unevenly around the bent part of the terminal, and when bent, the thickness of the terminal part of the product exceeds the limit of the thickness dimension, which may result in a defective product.

[0006] The present invention has been made to solve the above problems, and has an object to provide a method for manufacturing an electrolytic capacitor that can suppress thickness defects in the terminal portion. [Means for solving the problem]

[0007] A method for manufacturing an electrolytic capacitor of the present invention includes the steps of: preparing a workpiece including a sealing body in which an electrolytic capacitor element is sealed, a first lead frame connected to one of the anode and cathode of the electrolytic capacitor element, and a second lead frame connected to the other of the anode and the cathode; providing at least one step portion extending in the width direction of the first lead frame on at least one of a first main surface and a second main surface of the first lead frame; heat treating the workpiece; and cutting the first lead frame after the heat treatment, wherein the first lead frame has a base material made of Cu and has a low-melting-point metal layer on its surface made of a low-melting-point metal having a melting point lower than that of Cu, and the heat treatment is performed at a temperature higher than the melting point of the low-melting-point metal and lower than the melting point of Cu with the first lead frame with the step portion facing upward and the second lead frame facing downward, and the cutting step cuts the first lead frame between the sealing body and the step portion. Effect of the Invention

[0008] According to the present invention, it is possible to provide a method for manufacturing an electrolytic capacitor capable of suppressing thickness defects in terminal portions. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a plan view showing a schematic diagram of an example of a workpiece according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a perspective view that illustrates an example of a sealing body according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of the sealing body shown in FIG. 2 taken along line AA. [Figure 4] FIG. 4 is an enlarged cross-sectional view of the masked portion of the solid electrolytic capacitor element shown in FIG. [Diagram 5] FIG. 5 is a cross-sectional view of the workpiece shown in FIG. 1 taken along line AA. [Figure 6] FIG. 6 is a plan view that illustrates an example of a step for providing a step portion in the lead frame of the workpiece illustrated in FIG. [Figure 7] FIG. 7 is a cross-sectional view that illustrates an example of a step for providing a step portion in the lead frame of the workpiece illustrated in FIG. [Figure 8] FIG. 8 is a cross-sectional view that illustrates an example of a groove portion formed by irradiating a Sn layer with a laser. [Figure 9] FIG. 9 is a cross-sectional view that illustrates a schematic example of a step of providing a step portion in the lead frame of the workpiece illustrated in FIG. [Figure 10] FIG. 10 is a plan view illustrating an example of the workpiece illustrated in FIG. 6 after the heat treatment. [Figure 11] FIG. 11 is a cross-sectional view that illustrates an example of the workpiece illustrated in FIG. 7 after heat treatment. [Figure 12] FIG. 12 is a plan view that illustrates an example of a process for cutting the lead frame of the workpiece illustrated in FIG. [Figure 13] 13A to 13C are cross-sectional views that diagrammatically show an example of a process for cutting the lead frame of the workpiece shown in FIG. [Figure 14] 14A to 14C are cross-sectional views that diagrammatically show an example of a process for bending the lead frame of the workpiece shown in FIG. [Figure 15]FIG. 15 is a plan view that illustrates an example of a step of providing a second groove portion in the lead frame of the workpiece illustrated in FIG. [Figure 16] FIG. 16 is a cross-sectional view that illustrates an example of a step of providing a second groove portion in the lead frame of the workpiece illustrated in FIG. [Figure 17] 17A to 17C are cross-sectional views that diagrammatically show an example of a process for cutting the lead frame of the workpiece shown in FIG. [Figure 18] 18A to 18C are cross-sectional views that diagrammatically show an example of a process for bending the lead frame of the workpiece shown in FIG. [Figure 19] FIG. 19 is a cross-sectional view that typically illustrates still another example of the step of providing a step portion in the lead frame of the workpiece illustrated in FIG. [Figure 20] FIG. 20 is a plan view showing a schematic example of a workpiece according to a comparative embodiment of the present invention. [Figure 21] FIG. 21 is a plan view that illustrates an example of the workpiece illustrated in FIG. 20 after the heat treatment. [Figure 22] FIG. 22 is a cross-sectional view that illustrates an example of the workpiece illustrated in FIG. 20 after heat treatment. [Figure 23] FIG. 23 is a cross-sectional view that illustrates an example of a process for bending the lead frame of the workpiece illustrated in FIG. [Figure 24] FIG. 24 is a graph showing the thickness distribution of the anode terminal portion after heat treatment in Examples 1 and 2 and Comparative Example 1. [Diagram 25] FIG. 25 is a graph showing the defective product rates of defective anode terminals in Examples 1 and 2 and Comparative Example 1. [Figure 26] FIG. 26 is a side photograph of the solid electrolytic capacitor of Example 1. [Figure 27] FIG. 27 is a side photograph of the solid electrolytic capacitor of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A method for manufacturing an electrolytic capacitor will now be described. However, the present invention is not limited to the following configurations, and can be modified as appropriate within the scope of the present invention. Note that the present invention also includes a combination of two or more of the individual desirable configurations described below.

[0011] (Work preparation process) FIG. 1 is a plan view showing a schematic diagram of an example of a workpiece according to an embodiment of the present invention.

[0012] 1, first, a work 100 is prepared. The work 100 includes a plurality of sealing bodies 110, a lead frame 120 serving as a first lead frame, and a lead frame 130 serving as a second lead frame.

[0013] FIG. 2 is a perspective view that illustrates an example of a sealing body according to an embodiment of the present invention.

[0014] 2, a plurality of solid electrolytic capacitor elements 1 serving as electrolytic capacitor elements are sealed in each sealing body 110. Each solid electrolytic capacitor element 1 is covered with a sealing material 111.

[0015] Fig. 3 is a cross-sectional view of the sealing body shown in Fig. 2 taken along line AA. In Fig. 2 and Fig. 3, the length direction (longitudinal direction) of the sealing body 110 is indicated by L, the width direction by W, and the height direction by T. Here, the length direction L, the width direction W, and the height direction T are perpendicular to each other.

[0016] Sealing body 110 is formed by sealing a plurality of solid electrolytic capacitor elements 1 with sealing material 111. Sealing material 111 is formed so as to cover the entirety of each solid electrolytic capacitor element 1, a part of lead frame 120, and a part of lead frame 130. Examples of sealing material 111 include insulating resins such as epoxy resins.

[0017] The number of solid electrolytic capacitor elements 1 included in sealing body 110 is not particularly limited as long as it is one or more, and can be set appropriately.

[0018] The sealing body 110 has a substantially rectangular parallelepiped outer shape. The sealing body 110 has a first main surface 110a and a second main surface 110b that face each other in a height direction T, a first side surface 110c and a second side surface 110d that face each other in a width direction W, and a first end surface 110e and a second end surface 110f that face each other in a length direction L.

[0019] The first end face 110e and the second end face 110f may be V-shaped in cross section and slightly protrude outward as shown in FIGS.

[0020] The solid electrolytic capacitor element 1 comprises a valve action metal substrate 10 having a metal substrate layer 11 and a porous layer 12 on the metal substrate layer 11, the valve action metal substrate 10 having an anode leading region 13 and a cathode forming region 14, a dielectric layer (not shown in FIG. 3 ) provided on the surface of the porous layer 12 in the cathode forming region 14, a solid electrolyte layer 30 provided on the porous layer 12 in the cathode forming region 14 with the dielectric layer interposed therebetween, a conductive layer 40 formed on the solid electrolyte layer 30, and a mask 50 that separates the anode leading region 13 from the cathode forming region 14 and is provided on the porous layer 12 with the dielectric layer interposed therebetween.

[0021] On the anode lead-out region 13 side, the valve metal substrates 10 of the solid electrolytic capacitor elements 1 are held together by a lead frame 120 and led out of the sealing material 111 (sealing body 110).

[0022] On the cathode formation region 14 side, the conductive layers 40 of the solid electrolytic capacitor elements 1 are electrically connected, and further electrically connected to the lead frame 130, and are led out of the sealing material 111 (sealing body 110).

[0023] Each component of solid electrolytic capacitor element 1 will be described in detail below.

[0024] The valve metal substrate 10 is a thin film (foil) having a quadrangular shape in plan view, and is preferably a rectangular shape (strip shape) having a pair of long sides and a pair of short sides in plan view. The valve metal substrate 10 functions as the anode 60 of the solid electrolytic capacitor element 1.

[0025] FIG. 4 is an enlarged cross-sectional view of the masked portion of the solid electrolytic capacitor element shown in FIG.

[0026] As shown in Fig. 4, the valve metal substrate 10 has a metal substrate layer 11 and a porous layer 12 having a plurality of recesses. Therefore, each of the main surfaces of the valve metal substrate 10 is porous. This increases the surface area of ​​the valve metal substrate 10. Note that both main surfaces of the valve metal substrate 10 are not limited to being porous (porous layer 12), and only one of the main surfaces of the valve metal substrate 10 may be porous (porous layer 12).

[0027] The metal substrate layer 11 is the core metal portion of the valve metal substrate 10, and as shown in FIG. 3, its thickness is approximately constant.

[0028] The valve metal substrate 10 is made of a valve metal, such as an elemental metal such as aluminum, tantalum, niobium, titanium, zirconium, or an alloy containing these metals. An oxide film can be formed on the surface of the valve metal.

[0029] The valve action metal substrate 10 need only be composed of a metal substrate layer and a porous layer provided on at least one of the main surfaces of the metal substrate layer, and may be formed from a metal foil having an etched surface, a metal foil having a porous sintered powder body formed on the surface, or the like.

[0030] In this embodiment, the dielectric layer 20 is provided on the surface of the porous layer 12 of the valve metal substrate 10 (see FIG. 4). However, it is sufficient that the dielectric layer 20 is provided on at least one of the two main surfaces of the valve metal substrate 10.

[0031] The dielectric layer 20 is preferably made of an oxide film provided on the surface of the porous layer 12 of the valve metal substrate 10. For example, the dielectric layer 20 is made of an aluminum oxide. The aluminum oxide is formed by anodizing the surface of the valve metal substrate.

[0032] The mask 50 is an insulating member provided along one side (preferably a short side) of the valve metal base 10, and separates the anode 60 and the cathode 70 of the solid electrolytic capacitor element 1 to ensure insulation between the anode 60 and the cathode 70 of the solid electrolytic capacitor element 1. The mask 50 divides the valve metal base 10 into an anode extraction region 13 and a cathode formation region 14.

[0033] 4, the mask 50 is preferably provided so as to fill a plurality of pores (recesses) in the valve metal substrate 10 (porous layer 12). However, it is sufficient that part of the outer surface of the dielectric layer 20 is covered with the mask 50, and there may be pores (recesses) in the porous layer 12 that are not filled with the mask 50.

[0034] The mask 50 is made of an insulating material. The mask 50 is formed by applying a mask material such as a composition containing an insulating resin. Examples of the insulating resin include polyphenylsulfone (PPS), polyethersulfone (PES), cyanate ester resin, fluororesin (tetrafluoroethylene, tetrafluoroethylene-perfluoroalkylvinylether copolymer, etc.), a composition of soluble polyimidesiloxane and epoxy resin, polyimide resin, polyamideimide resin, and derivatives or precursors thereof.

[0035] The mask material can be applied by, for example, screen printing, roller transfer, dispenser, inkjet printing, or the like.

[0036] The solid electrolytic capacitor element 1 has a solid electrolyte layer 30 provided on a dielectric layer 20 and a conductive layer 40 provided on the solid electrolyte layer 30, which function as a cathode 70 of the solid electrolytic capacitor element 1. The cathode 70 is provided on the dielectric layer 20 in a cathode-forming region 14 of the valve metal base 10 defined by a mask 50.

[0037] The solid electrolyte layer 30 is provided on the dielectric layer 20 in the cathode formation region 14 of the valve metal substrate 10, which is defined by a mask 50. As shown in Fig. 4, the solid electrolyte layer 30 is preferably provided so as to fill a plurality of pores (recesses) of the valve metal substrate 10 (porous layer 12). However, it is sufficient that part of the outer surface of the dielectric layer 20 is covered with the solid electrolyte layer 30, and there may be pores (recesses) of the porous layer 12 that are not filled with the solid electrolyte layer 30.

[0038] Materials constituting the solid electrolyte layer 30 include conductive polymers such as polypyrroles, polythiophenes, and polyanilines. Among these, polythiophenes are preferred, and poly(3,4-ethylenedioxythiophene), also known as PEDOT, is particularly preferred. The conductive polymers may contain dopants such as polystyrene sulfonate (PSS).

[0039] The solid electrolyte layer 30 is formed, for example, by a method of forming a polymerized film of a conductive polymer such as poly(3,4-ethylenedioxythiophene) on the surface of the dielectric layer 20 using a liquid containing a polymerizable monomer such as 3,4-ethylenedioxythiophene, or a method of applying a dispersion liquid of a conductive polymer such as poly(3,4-ethylenedioxythiophene) to the surface of the dielectric layer 20 and drying it.

[0040] It is preferable to form an outer layer that covers the entire dielectric layer 20 after forming an inner layer that fills the pores (recesses) of the valve metal substrate 10. The inner layer can be formed by, for example, a dipping method, electrolytic polymerization, sponge transfer, screen printing, a dispenser, inkjet printing, etc. Similarly, the outer layer can be formed by, for example, a dipping method, electrolytic polymerization, sponge transfer, screen printing, a dispenser, inkjet printing, etc.

[0041] The conductive layer 40 is provided on the solid electrolyte layer 30. The conductive layer 40 covers substantially the entire area of ​​the solid electrolyte layer 30 and is in contact with the mask 50. The conductive layer 40 may be disposed so as to cover at least a portion of the mask 50, or may be disposed up to the front of the mask 50 without contacting the mask 50. The conductive layer 40 has a substantially constant thickness.

[0042] The conductive layer 40 includes, for example, a carbon layer or a cathode conductor layer. The conductive layer 40 may also be a composite layer in which a cathode conductor layer is provided on the outer surface of a carbon layer, or a mixed layer including carbon and a cathode conductor layer material.

[0043] The carbon layer is formed, for example, by a method in which a carbon paste containing carbon particles and resin is applied to the surface of the solid electrolyte layer 30 and then dried.

[0044] The carbon paste can be applied by, for example, a dipping method, sponge transfer, screen printing, spray application, a dispenser, inkjet printing, or the like.

[0045] The cathode conductor layer is formed, for example, by a method of applying a conductive paste containing metal particles such as gold, silver, copper, platinum, etc. and a resin to the surface of the solid electrolyte layer or the carbon layer and drying it. The cathode conductor layer is preferably a silver layer.

[0046] The conductive paste can be applied by, for example, a dipping method, sponge transfer, screen printing, spray application, a dispenser, inkjet printing, or the like.

[0047] Next, the lead frames 120 and 130 will be described in detail below.

[0048] The lead frames 120 and 130 are thin metal plates that support and fix the multiple sealing bodies 110, and are components that serve as connection terminals when mounting each sealing body 110. The lead frames 120 and 130 are provided parallel to the first main surface 110a and the second main surface 110b of the sealing body 110. As shown in FIG. 3, the lead frame 120 has a first main surface 120a on the first main surface 110a side of the sealing body 110, and a second main surface 120b on the second main surface 110b side of the sealing body 110. Similarly, the lead frame 130 has a first main surface 130a on the first main surface 110a side of the sealing body 110, and a second main surface 130b on the second main surface 110b side of the sealing body 110.

[0049] The lead frame 120 is connected to the valve metal base 10 of each solid electrolytic capacitor element 1, i.e., the anode 60. More specifically, as shown in FIG. 1, the lead frame 120 has a plurality of anode terminals 121 provided corresponding to the plurality of sealing bodies 110, and a connecting portion 122 supporting the plurality of anode terminals 121. Each anode terminal 121 is a portion for forming an anode terminal of the solid electrolytic capacitor, and is connected to the anode 60 of the solid electrolytic capacitor element 1 included in the corresponding sealing body 110. Each anode terminal 121 is formed, for example, in a rectangular shape in a plan view, and extends straight in one direction from the corresponding sealing body 110 (first end surface 110e). The connecting portion 122 is connected to the plurality of anode terminals 121, and extends in the width direction w1 of the lead frame 120. Width direction w1 of lead frame 120 is the width direction of multiple anode terminals 121, and the width direction of anode terminals 121 is the direction perpendicular to the extension direction of anode terminals 121 (direction away from sealing body 110).

[0050] The lead frame 130 is connected to the conductive layer 40, i.e., the cathode 70, of each solid electrolytic capacitor element 1. More specifically, as shown in FIG. 1, the lead frame 130 has a plurality of cathode terminals 131 provided corresponding to the plurality of sealing bodies 110, and a connecting portion 132 supporting the plurality of cathode terminals 131. Each cathode terminal 131 is a portion for forming a cathode terminal of the solid electrolytic capacitor, and is connected to the cathode 70 of the solid electrolytic capacitor element 1 included in the corresponding sealing body 110. Each cathode terminal 131 is formed, for example, in a rectangular shape in a plan view, and extends straight from the corresponding sealing body 110 (second end surface 110f) toward the other side. The connecting portion 132 is connected to the plurality of cathode terminals 131, and extends in the width direction w2 of the lead frame 130. Width direction w2 of lead frame 130 is the width direction of multiple cathode terminals 131, and the width direction of cathode terminals 131 is a direction perpendicular to the extension direction of cathode terminals 131 (direction away from sealing body 110).

[0051] Fig. 5 is a cross-sectional view of the workpiece taken along line AA in Fig. 1. Note that the internal structure of sealing body 110 is omitted in Fig. 5. Also, lead frame 130 has a cross-sectional structure similar to that of lead frame 120 shown in Fig. 5, and therefore is omitted from the drawing.

[0052] 5, each of the lead frames 120 and 130 has a base material (hereinafter referred to as a Cu base material) 140 made of Cu (copper), and has a Sn layer 141 as a low melting point metal layer on the surface. The Sn layer 141 is made of Sn (tin) as a low melting point metal having a melting point lower than that of Cu.

[0053] Thus, the Sn layer 141 is suitable as the low melting point metal layer, and the lead frames 120 and 130 preferably have a Ni layer 142 made of Ni (nickel) between the Cu base material 140 and the Sn layer 141. That is, the lead frames 120 and 130 each preferably have a Cu base material 140, a Ni layer 142 formed on the surface of the Cu base material 140, and a Sn layer 141 formed on the surface of the Ni layer 142. This allows a groove that effectively functions as a step portion to be formed by laser irradiation, as described later. In addition, the Sn layer 141 can improve the wettability with solder. Furthermore, the Ni layer 142 functions as a barrier layer that prevents the reaction between the Cu base material 140 and the Sn layer 141.

[0054] The Cu base 140 can be formed, for example, by laser processing or punching a thin Cu plate. The Sn layer 141 and the Ni layer 142 can each be formed, for example, by a plating method.

[0055] The thickness of the Cu base 140 is preferably 90 μm or more and 110 μm or less.

[0056] The thickness of the Sn layer 141 is preferably not less than 5.0 μm and not more than 7.0 μm.

[0057] The thickness of the Ni layer 142 is preferably 0.5 μm or more and 2.0 μm or less.

[0058] (Step formation process) Fig. 6 is a plan view showing a schematic example of a process for providing a step portion in the lead frame of the work shown in Fig. 1. Fig. 7 is a cross-sectional view showing a schematic example of a process for providing a step portion in the lead frame of the work shown in Fig. 1. Fig. 7 corresponds to a cross-sectional view of the work shown in Fig. 1 taken along line BB. Also, the internal structure of sealing body 110 is not shown in Fig. 7.

[0059] 6 and 7, a step portion 150 extending in the width direction w1 of the lead frame 120 is then provided on the second main surface 120b of the lead frame 120. More specifically, in each anode terminal portion 121, a step portion 150 extending in the width direction w1 of the lead frame 120, i.e., in the width direction of the anode terminal portion 121, is provided on the second main surface 120b of the lead frame 120. The step portion 150 is formed from one end to the other end of the anode terminal portion 121 in the width direction w1. The width direction w1 of the lead frame 120 may be parallel to the width direction W of the sealing body 110.

[0060] It is preferable to form a groove portion (first groove portion) 151 as the step portion 150. That is, it is preferable to form a linear recessed portion on the surface of the lead frame 120.

[0061] FIG. 8 is a cross-sectional view that illustrates an example of a groove portion formed by irradiating a Sn layer with a laser.

[0062] The grooves 151 may be scratched portions formed on the lead frame 120. Specifically, the grooves 151 may be formed, for example, by mechanically scraping the surface of the lead frame 120, but are preferably formed by irradiating the Sn layer 141, i.e., the low melting point metal layer, with a laser to melt it, as shown in FIG. 8. This allows the Sn to be effectively blocked by the grooves 151 even if the Sn melts and flows in the heat treatment process described below. This is thought to be because the surfaces of the Sn layer 141 and Ni layer 142 newly formed by the laser irradiation are oxidized to form oxide layers (for example, an SnO layer and an Ni2O3 layer), and the wettability between different oxides is usually low.

[0063] From this viewpoint, it is preferable to form groove 151 by linearly removing Sn layer 141 so as to expose the surface of Ni layer 142. As a result, groove 151 is formed whose bottom surface is made of Ni layer 142 and whose side surface is made of Sn layer 141, as shown in Fig. 8, so that the flow of Sn can be effectively blocked by the oxide layer of Sn layer 141 and Ni layer 142 as described above.

[0064] As the laser, for example, a solid-state laser such as a YAG (yttrium aluminum garnet) laser can be used. The laser irradiation conditions are not particularly limited and can be set appropriately, but are preferably such that only the Sn layer 141 melts and the Ni layer 142 and the Cu base material 140 do not melt. Since the melting point of Sn is 231°C, the melting point of Ni is 1455°C, and the melting point of Cu is 1085°C, it is preferable to heat the surface temperature of the lead frame 120 to a temperature higher than 231°C and lower than 1085°C by the above-mentioned laser irradiation.

[0065] Specifically, the laser output is preferably 4.5W or more and 6.5W or less.

[0066] The laser scanning speed was set to 300 mm / s.

[0067] The laser frequency was set to 20 kHz.

[0068] Fig. 9 is a cross-sectional view that illustrates another example of a process for providing a step portion in the lead frame of the workpiece illustrated in Fig. 1. Fig. 9 corresponds to a cross-sectional view of the workpiece taken along line BB illustrated in Fig. 1. Also, in Fig. 9, the internal structure of sealing body 110 is omitted from illustration.

[0069] The surface on which the step portion 150 is formed is not particularly limited as long as it is the first main surface 120a and / or the second main surface 120b of the lead frame 120, and for example, as shown in Fig. 9, the step portion 150 may be formed on each of the first main surface 120a and the second main surface 120b of the lead frame 120. In this case, the step portion 150 on the first main surface 120a side and the step portion 150 on the second main surface 120b side may be formed in substantially the same place or in different places.

[0070] Although the case where one step portion 150 is provided on each main surface of each anode terminal 121 has been described here, two or more step portions 150 may be provided on each main surface of each anode terminal 121.

[0071] Further, although the case where the step portion 150 is linear has been described here, the planar shape of the step portion 150 is not particularly limited, and may be, for example, a curved shape such as an arc or a wavy line, or a broken line such as a zigzag line.

[0072] (Heat treatment process) Next, the work 100 is subjected to a heat treatment (aging treatment). In detail, as shown in Fig. 6, the work 100 is heat-treated at a temperature higher than the melting point of Sn, i.e., the melting point of the low-melting point metal, and lower than the melting point of Cu, with the lead frame 120 provided with the step portion 150 facing upward and the lead frame 130 facing downward. That is, during the heat treatment, the lead frame 120, the sealing body 110, and the lead frame 120 are arranged in this order in the vertical direction. This allows screening of individuals with poor quality.

[0073] The peak temperature of the heat treatment is preferably 260°C or higher and 270°C or lower.

[0074] The heat treatment time is preferably from 150° C. to 200° C. for from 60 to 120 seconds, and more preferably from 217° C. or higher for from 60 to 150 seconds.

[0075] Fig. 10 is a plan view showing an example of the workpiece shown in Fig. 6 after heat treatment, and Fig. 11 is a cross-sectional view showing an example of the workpiece shown in Fig. 7 after heat treatment.

[0076] As shown in Figs. 10 and 11, in the heat treatment process, the temperature of the heat treatment is higher than the melting point of Sn, which is a low melting point metal, so that Sn melts during the heat treatment, and Sn constituting the Sn layer 141 flows downward due to gravity. However, since the lead frame 120 is provided with the step portion 150, the flow of Sn can be blocked at the step portion 150 (see Sn 141a in Figs. 10 and 11). That is, in the lead frame 120 located at the top, the amount of Sn (low melting point metal) that gathers near the sealing body 110 can be reduced compared to the case where the step portion 150 is not present (see Sn 141b in Figs. 10 and 11). As a result, the thickness of the terminal formed from the lead frame 120, here the anode terminal, can be reduced, and the thickness defect of the anode terminal portion of the solid electrolytic capacitor to be manufactured can be suppressed.

[0077] In addition, since lead frame 130 is located below sealing body 110 in the heat treatment process, even if Sn constituting Sn layer 141 flows downward due to gravity, the Sn does not gather near sealing body 110. Therefore, lead frame 130 does not need to have a step portion unlike lead frame 120.

[0078] (cutting process) Fig. 12 is a plan view that illustrates an example of a process for cutting the lead frame of the workpiece illustrated in Fig. 10. Fig. 13 is a cross-sectional view that illustrates an example of a process for cutting the lead frame of the workpiece illustrated in Fig. 11.

[0079] 12 and 13, the lead frames 120 and 130 are cut after the heat treatment. More specifically, the lead frame 120 is cut between each sealing body 110 and each step portion 150. That is, each anode terminal portion 121 is cut between the corresponding sealing body 110 and the step portion 150 provided on the anode terminal portion 121. Also, each cathode terminal portion 131 is cut to have the same length as the corresponding anode terminal portion 121. This removes unnecessary portions of the lead frames 120 and 130, such as the connecting portion 122 and the connecting portion 132 (see FIG. 1).

[0080] (Terminal formation process) 14A to 14C are cross-sectional views that diagrammatically show an example of a process for bending the lead frame of the workpiece shown in FIG.

[0081] Finally, as shown in Fig. 14, the cut lead frames 120 and 130 are each folded. More specifically, for each sealing body 110, the anode terminal portion 121 is folded approximately 90° at the approximate center, and then the anode terminal portion 121 is folded approximately 90° at the base portion. This forms an anode terminal 123 along the sealing body 110. The cathode terminal portion 131 is also folded in the same manner, thereby forming a cathode terminal 133. As a result, the solid electrolytic capacitor 160 is completed.

[0082] In this embodiment, since an increase in the thickness of the anode terminal 123 caused by molten Sn (a low melting point metal) can be suppressed, thickness defects in the region where the anode terminal 123 is present can be suppressed.

[0083] Other variations of this embodiment will now be described.

[0084] Fig. 15 is a plan view showing a schematic example of a process for providing a second groove portion in the lead frame of the work shown in Fig. 1. Fig. 16 is a cross-sectional view showing a schematic example of a process for providing a second groove portion in the lead frame of the work shown in Fig. 1. Fig. 16 corresponds to a cross-sectional view of the work taken along line BB shown in Fig. 1. Also, the internal structure of sealing body 110 is not shown in Fig. 16.

[0085] As shown in FIG. 15 and FIG. 16, in the step forming step, a second groove 152 (linear concave stripe) may be formed in the width direction w1 of the lead frame 120 between the step 150 and the sealing body 110. More specifically, in each anode terminal 121, a linear second groove 152 extending in the width direction w1 of the lead frame 120, i.e., in the width direction of the anode terminal 121, is provided in the first main surface 120a of the lead frame 120. As a result, the second groove 152 is formed parallel to the width direction W of the sealing body 110. The second groove 152 is formed from one end to the other end of the anode terminal 121 in the width direction w1. The second groove 152 is formed at a position along a ridge line where the second main surface 110b and the first end surface 110e of the sealing body 110 intersect when the lead frame 120 is folded.

[0086] The second groove 152 may be formed, for example, by mechanically scraping the surface of the lead frame 120, but is preferably formed by irradiating the Sn layer 141, i.e., the low-melting point metal layer, with a laser to melt it, in the same manner as the groove (first groove) 151. More specifically, the second groove 152 is preferably formed by linearly removing the Sn layer 141 so that the surface of the Ni layer 142 is exposed.

[0087] 17A to 17C are cross-sectional views that diagrammatically show an example of a process for cutting the lead frame of the workpiece shown in FIG.

[0088] 17, in a cutting step following a heat treatment step, the lead frame 120 may be cut between the step 150 and the second groove 152. More specifically, each anode terminal 121 is cut between the step 150 and the second groove 152 provided in that anode terminal 121.

[0089] In addition, the second groove portion 152, like the step portion 150, also has the function of blocking the flow of Sn, which is a low-melting point metal, in the heat treatment process (see Sn 141c in FIG. 17).

[0090] 18A to 18C are cross-sectional views that diagrammatically show an example of a process for bending the lead frame of the workpiece shown in FIG.

[0091] 18, in the terminal forming step, the cut lead frame 120 may be bent along the second groove portion 152. Since the lead frame 120 is thin at the second groove portion 152, the bending process can be easily performed. More specifically, for each sealing body 110, the anode terminal portion 121 is bent at approximately 90° at the second groove portion 152 (usually approximately at the center of the anode terminal portion 121), and then the anode terminal portion 121 is bent at approximately 90° at the base portion.

[0092] Here, we have described the case where the second groove portion 152 is provided on the first main surface 120a of the lead frame 120, i.e., the main surface located opposite the bending direction of the lead frame 120. However, the second groove portion 152 may also be provided on the main surface of the lead frame 120 that is to be bent, i.e., the second main surface 120b.

[0093] Similarly, the lead frame 130 may also be provided with a groove for bending.

[0094] Fig. 19 is a cross-sectional view that illustrates a schematic diagram of yet another example of a step of providing a step portion in the lead frame of the workpiece illustrated in Fig. 1. Fig. 19 corresponds to a cross-sectional view of the workpiece taken along line BB illustrated in Fig. 1. Also, in Fig. 19, the internal structure of sealing body 110 is omitted from illustration.

[0095] 19, a protrusion 153 may be formed as the step portion 150. For example, a linear convex portion may be formed on the surface of the lead frame 120. This also makes it possible for the protrusion 153 to block the flow of Sn, which is a low-melting point metal, in the heat treatment process.

[0096] The protrusion 153 may be formed, for example, by locally increasing the thickness of the Cu base material 140. Alternatively, the Cu base material 140 may be pressed from one side to protrude to the other side, thereby simultaneously forming a groove on the opposite side of the protrusion 153. In this case, both the protrusion 153 and the groove function as the step portion 150.

[0097] In this manner, the step portion 150 may be a combination of one or more grooves and one or more protrusions.

[0098] In the above embodiment, a case has been described in which the step portion 150 is provided on the lead frame 120 connected to the anode 60 of the solid electrolytic capacitor element 1, and the heat treatment of the workpiece 100 is performed in a state in which the lead frame 120 is on the upper side and the lead frame 130 connected to the cathode 70 of the solid electrolytic capacitor element 1 is on the lower side, but the heat treatment of the workpiece 100 may be performed in a state in which the workpiece 100 is turned upside down, i.e., in a state in which the lead frame 130 connected to the cathode 70 of the solid electrolytic capacitor element 1 is on the upper side and the lead frame 120 connected to the anode 60 of the solid electrolytic capacitor element 1 is on the lower side. In this case, the step portion 150 may be provided in the lead frame 130.

[0099] In addition, in the above embodiment, the electrolytic capacitor element has been described as a solid electrolytic capacitor using a conductive polymer as the electrolyte material, but the electrolytic capacitor element in the present invention may be an electrolytic capacitor element that uses an electrolyte solution as the electrolyte material, or may be a so-called hybrid type electrolytic capacitor element that uses an electrolyte solution together with a solid electrolyte such as a conductive polymer as the electrolyte material.

[0100] (Comparative form) FIG. 20 is a plan view showing a schematic example of a workpiece according to a comparative embodiment of the present invention.

[0101] The workpiece 100A shown in FIG. 20 is substantially the same as the workpiece 100 shown in FIG. 6, except that the step portion 150 is not provided.

[0102] Next, similarly to the above embodiment, the workpiece 100A is subjected to a heat treatment (aging treatment).

[0103] Fig. 21 is a plan view showing an example of the workpiece shown in Fig. 20 after heat treatment. Fig. 22 is a cross-sectional view showing an example of the workpiece shown in Fig. 20 after heat treatment. Fig. 23 is a cross-sectional view showing an example of a step of bending the lead frame of the workpiece shown in Fig. 22.

[0104] In this comparative example, the workpiece 100A without the step portion 150 is subjected to the heat treatment as it is, so that Sn melts during the heat treatment and flows downward due to gravity. Therefore, after the heat treatment, in the lead frame 120 located at the top, Sn gathers in large amounts near the sealing body 110 (see Sn 141d in FIGS. 21 and 22). As a result, as shown in FIG. 23, the thickness of the terminal formed from the lead frame 120, here the anode terminal 123, becomes large, and there is a risk of a thickness defect occurring in the anode terminal portion of the manufactured solid electrolytic capacitor 160A.

[0105] The present specification discloses the following:

[0106] <1> A step of preparing a work including a sealing body in which an electrolytic capacitor element is sealed, a first lead frame connected to one of an anode and a cathode of the electrolytic capacitor element, and a second lead frame connected to the other of the anode and the cathode; providing at least one step portion extending in a width direction of the first lead frame on at least one of a first main surface and a second main surface of the first lead frame; A step of performing heat treatment on the workpiece; cutting the first lead frame after the heat treatment; the first lead frame has a base material made of Cu and a low-melting-point metal layer on a surface thereof made of a low-melting-point metal having a melting point lower than that of Cu; the heat treatment is performed at a temperature higher than the melting point of the low-melting point metal and lower than the melting point of Cu in a state in which the first lead frame having the stepped portion is placed above and the second lead frame is placed below; A method for manufacturing an electrolytic capacitor, wherein in the cutting step, the first lead frame is cut between the sealing body and the step portion.

[0107] <2> A first groove portion is formed as the step portion. <1> A method for producing the electrolytic capacitor according to claim 1.

[0108] <3> The low-melting point metal layer is irradiated with a laser to melt the low-melting point metal layer, thereby forming the first groove portion. <2> A method for producing the electrolytic capacitor according to claim 1.

[0109] <4> The low-melting-point metal layer is a Sn layer made of Sn as the low-melting-point metal, the first lead frame has a Ni layer made of Ni between the base material and the Sn layer, The Sn layer is linearly removed so as to expose a surface of the Ni layer, thereby forming the first groove portion. <2> or <3> A method for producing the electrolytic capacitor according to claim 1.

[0110] <5> A protrusion is formed as the step portion. <1> from <4> 13. A method for producing the electrolytic capacitor according to claim 12.

[0111] <6> providing the step portion on each of the first main surface and the second main surface of the first lead frame; <1> from <5> 13. A method for producing the electrolytic capacitor according to claim 12.

[0112] <7> a second groove portion is formed in the width direction of the first lead frame between the step portion and the sealing body; In the cutting step, the first lead frame is cut between the step portion and the second groove portion, further comprising a step of bending the cut first lead frame along the second groove portion. <1> from <6> 13. A method for producing the electrolytic capacitor according to claim 12. EXAMPLES

[0113] EXAMPLES Hereinafter, examples will be given that more specifically disclose the method for producing an electrolytic capacitor according to the present invention, however, the present invention is not limited to these examples.

[0114] Example 1 In Example 1, a workpiece similar to the workpiece 100 according to the embodiment shown in Fig. 1 was prepared. That is, this workpiece had a plurality of sealing bodies, a first lead frame, and a second lead frame, and a plurality of solid electrolytic capacitor elements were sealed in each sealing body, and each of the first lead frames was connected to the anode of each solid electrolytic capacitor element of the corresponding sealing body, and each of the second lead frames was connected to the cathode of each solid electrolytic capacitor element of the corresponding sealing body. Each of the first lead frame and the second lead frame had a Cu base material, a Ni layer formed on the surface of the Cu base material, and a Sn layer formed on the surface of the Ni layer.

[0115] Then, one main surface of each anode terminal of the first lead frame was irradiated with a laser to form a linear groove in the width direction of the anode terminal. The laser irradiation conditions were power: 5.5±0.1 W, scan speed: 300 mm / s, and frequency: 20 kHz. As a result, as shown in FIG. 8, the Sn layer was melted and removed to expose the surface of the Ni layer, and a linear groove was formed. At this time, the Ni layer and the Cu base material were not affected by the laser irradiation.

[0116] Next, with the first lead frame facing up and the second lead frame facing down, the workpiece was heat-treated at a peak temperature of 260°C or higher and 270°C or lower, with a time of 150°C or higher and 200°C or lower being 60 seconds or higher and 120 seconds or lower, and a time of 217°C or higher being 60 seconds or higher and 120 seconds or lower.

[0117] Then, the first lead frame and the second lead frame were cut. More specifically, each anode terminal was cut between the corresponding sealing body and the step provided on the anode terminal. Also, each cathode terminal was cut to have the same length as the corresponding anode terminal.

[0118] Then, the cut first lead frame and the cut second lead frame were folded to form an anode terminal and a cathode terminal, respectively, thereby producing the solid electrolytic capacitor of Example 1.

[0119] Example 2 The solid electrolytic capacitor of Example 2 was produced in the same manner as Example 1, except that a laser was irradiated onto each of the two main surfaces of each anode terminal portion of the first lead frame to form linear grooves on each of the main surfaces. The grooves were formed in the same locations on each of the main surfaces.

[0120] Comparative Example 1 A solid electrolytic capacitor of Comparative Example 1 was produced in the same manner as in Example 1, except that no grooves were formed in the anode terminal portions of the first lead frame.

[0121] (Measurement of thickness of anode terminal) For the solid electrolytic capacitors according to Examples 1 and 2 and Comparative Example 1, the thicknesses of a plurality of anode terminals (specifically, 32 anode terminals) after the heat treatment were measured near the sealing body (point P in FIG. 10). The results are shown in Table 1 below and FIG.

[0122] FIG. 24 is a graph showing the distribution of thicknesses of anode terminals after heat treatment in Examples 1 and 2 and Comparative Example 1.

[0123] [Table 1]

[0124] The target thickness of the anode terminal here was 170 μm or less, but in Examples 1 and 2 in which grooves were formed on one or both sides of the first lead frame, the target thickness could be achieved. On the other hand, in Comparative Example 1 in which no grooves were formed, the target thickness could not be achieved.

[0125] (Calculation of defective product rate) The defective rate of anode terminals was calculated for the solid electrolytic capacitors according to Examples 1 and 2 and Comparative Example 1. A defective anode terminal is a dimensional defect in which the dimension in the thickness direction of the solid electrolytic capacitor at the anode terminal portion exceeds the target. Here, 160 solid electrolytic capacitors were produced for each Example and Comparative Example, and the rate of defective anode terminals among them was calculated.

[0126] FIG. 25 is a graph showing the defective product rates of defective anode terminals in Examples 1 and 2 and Comparative Example 1.

[0127] 25, in Examples 1 and 2, the defective rate was low, and in particular in Example 2 in which grooves were formed on both sides of the first lead frame, the defective rate was reduced to 0%. On the other hand, in Comparative Example 1 in which no grooves were formed, the defective rate was high, exceeding 30%.

[0128] (Side view of solid electrolytic capacitor) Fig. 26 is a side view photograph of the solid electrolytic capacitor of Example 1. Fig. 27 is a side view photograph of the solid electrolytic capacitor of Comparative Example 1.

[0129] As shown in Fig. 26, in Example 1, the anode terminal is thin, and as a result, it is possible to prevent the thickness of the solid electrolytic capacitor from increasing at the anode terminal. In contrast, in Comparative Example 1, the anode terminal is thick, and as a result, it is clear that the thickness of the solid electrolytic capacitor increases at the anode terminal as shown in Fig. 27. [Explanation of symbols]

[0130] 1 Solid electrolytic capacitor element 10 Valve metal substrate 11 Metal substrate layer 12 Porous layer 13 Anode Extraction Area 14 Cathode formation area 20 Dielectric layer 30 Solid electrolyte layer 40 Conductive Layer 50 Mask 60 Anode 70 Cathode 100 Work 110 Sealing body 110a: First main surface of sealing body 110b Second main surface of sealing body 110c: First side surface of encapsulant 110d second side of encapsulant 110e: first end surface of sealing body 110f: second end surface of sealing body 111 Encapsulating materials 120, 130 Lead frame 120a, 130a First main surface of lead frame 120b, 130b Second main surface of lead frame 121 Anode terminal section 122, 132 connection part 123 Anode terminal 131 Cathode terminal 133 Cathode terminal 140 Base material (Cu base material) 141 Sn layer 141a, 141b, 141c Sn 142 Ni layer 150 Step 151 Groove (first groove) 152 Second groove 153 Protrusion 160, 160A Solid Electrolytic Capacitor

Claims

1. A step of preparing a work including a sealing body in which an electrolytic capacitor element is sealed, a first lead frame connected to one of an anode and a cathode of the electrolytic capacitor element, and a second lead frame connected to the other of the anode and the cathode; providing at least one step portion extending in a width direction of the first lead frame on at least one of a first main surface and a second main surface of the first lead frame; A step of performing heat treatment on the workpiece; cutting the first lead frame after the heat treatment; the first lead frame has a base material made of Cu and a low-melting-point metal layer on a surface thereof made of a low-melting-point metal having a melting point lower than that of Cu; the heat treatment is performed at a temperature higher than the melting point of the low-melting point metal and lower than the melting point of Cu in a state where the first lead frame having the stepped portion is placed above and the second lead frame is placed below; The method for manufacturing an electrolytic capacitor, wherein in the cutting step, the first lead frame is cut between the sealing body and the step portion.

2. The method for manufacturing an electrolytic capacitor according to claim 1 , wherein a first groove portion is formed as the step portion.

3. The method for manufacturing an electrolytic capacitor according to claim 2 , wherein the first groove portion is formed by irradiating the low melting point metal layer with a laser to melt the low melting point metal layer.

4. The low-melting-point metal layer is a Sn layer made of Sn as the low-melting-point metal, the first lead frame has a Ni layer made of Ni between the base material and the Sn layer, 4. The method for producing an electrolytic capacitor according to claim 2, wherein the first groove portion is formed by removing the Sn layer linearly so as to expose a surface of the Ni layer.

5. The method for manufacturing an electrolytic capacitor according to claim 1 , wherein a protrusion is formed as the step portion.

6. The method for manufacturing an electrolytic capacitor according to claim 1 , wherein the step portion is provided on each of the first main surface and the second main surface of the first lead frame.

7. a second groove portion is formed in the width direction of the first lead frame between the step portion and the sealing body; In the cutting step, the first lead frame is cut between the step portion and the second groove portion, 3. The method for manufacturing an electrolytic capacitor according to claim 1, further comprising the step of bending the cut first lead frame along the second groove portion.

Citation Information

Patent Citations

  • Semiconductor device

    JP1990109356A

  • Lead frame and semiconductor device

    JP1993291467A

  • Solid electrolytic capacitor

    JP2009064808A

  • Electronic component, wiring board and electronic apparatus

    JP2021118297A

  • Solid electrolytic capacitor and method for manufacturing same

    WO2007052652A1